A case of long-term tolerance after kidney transplantation - A. A. Korzhenevsky; N. P. Korzhenevskaya (Медицинская иммунология, 2022)
We present a case of long-term organ functioning (ca.10 years) after allografting of a cadaveric kidney without usage of immunosuppressing drugs. In 2005, a patient suffering from a hypertensive form of chronic glomerulonephritis, have received an allogeneic graft of cadaveric kidney compatible for AB0 system, HLA antigens (A19, B07, DR04), and negative results of cross-match test. The graft function was immediately restored, with normalization of creatinine levels achieved 4-5 days after surgery. Immunosuppression with cyclosporine, solumedrol, cellсept, metypred and simulect was performed in the hospital. Pulse therapy with solumedrol was performed on the day +20 due to the development of initial rejection signs. The postoperative period proceeded without infectious complications. The patient was discharged being recommended to take cyclosporine, Cell-Sept and Metypred. Within a year after transplantation, the patient claimed for pain in the hip joint, and, therefore, metypred was completely canceled. Subsequently, the Cellcept was replaced with a Mayfortic. In 2007, the signs of coxarthrosis were revealed at computed tomography, followed by aseptic necrosis of the the right femur head. Deforming osteoarthritis of the right hip joint was detected, and the hip replacement surgery was suggested. In 2010, due to risk of side effects from ongoing immunosuppressive therapy, e.g., joint damage, the Mayfortic was canceled. In 2012, being in fear of original Sandimmun Neoral replacement by a generic drug, the patient completely refused cyclosporine therapy. In 2021, the endoprosthetics of the right hip joint was performed, and the surgical wound healed initially. Since 2012, the patient has not completely taken immunosuppressive therapy. Over this time period, the patient has never been admitted to the hospital for impaired functioning of the organ graft. Meanwhile, he monitored his graft function on regular basis undergoing biochemical analyses, clinical examination, ultrasound studies of the graft and made regular visits to the outpatient department. In 2021, a week after hip replacement, there was a slight increase in serum creatinine, followed by further increase to 230 mmol/L in 2021, and to 310 mmol/L in March 2022. In February 2022, the patient suffered mild respiratory infection (confirmed COVID-19). In March 2022, the first clinical signs of increasing nephropathy appeared, i.e., swelling of both lower extremities, with leukocytes in urine upon routine analysis, increased blood flow resistance in the main artery of the transplant shown by ultrasound study. Due to worsening of the patient’s condition, he resumed taking the prescribed immunosuppressants.